Geopolitics of Chaos and Geopolitical Vacuum: Current conflicts in the global geopolitical order of power - Despotović, Ljubiša (Napredak, 2025)
The paper elaborates on the current geopolitical issues with potential far-reaching consequences for establishing the future order of power in international relations, as well as on the geopolitical powers themselves. The paper will analyze primarily the existing and potential crisis hotspots, as well as the changes occurring after US President Donald Trump came to power, and anticipations of potential results and consequences of the changes he initiated in his second presidential mandate. Moreover, attention will also be drawn to the analysis of the current position of large geopolitical powers with the already proven status of rivals, competitors and disputers of decades-long domination and hegemony of the Atlanticist West. In addition, we will try to answer the question about the possible end of the globalization era and the potential emergence of the post-globalization order.
Keywords: geopolitics; international order; power; crisis hotspots; globalization